O impacto do SIMPLES na geração de emprego no período 1995 - 2005: uma análise do setor de confecções e artefatos de tecidos - Souza, Walkíria Guedes de (2008)
This dissertation analyses the Simples’ effects on job creation and the number of establishments in the 1995 – 2005 period for the Garment industry. Two sub-periods are also analysed: 1995 – 2000 and 200 – 2005. The data base in the Annual Relation o Social Information (RAIS) as produced by the Ministry of Labour (MTE). The variables used are the: average wage, number of registered labor, as also dummies variables for estimating the spatial and temporal effects of that program. Descritive statistics and pooling regression analysis are used to assess those impacts. The results shows that the South and Southeast regions concentrates a larger proportion of job creation and establishments. They also indicate a great increase in the number of registered labor for the set of Micro’s and Small enterprises (MPE’s) for the industry under study following the Simples. The regional and temporal impacts have in general the expected signs and are statistically significant, in particular, for the South and Southeast regions. The temporal impacts are greater for the 2000 – 2005 sub – periods, indicating on increasing adoption of the Simples by the MPE’s. Finally, in spite of some limitations of the model and of the number of variables used, we can conclude that the Simples do have a positive effect on job creation and on the number of establishments for the MPE’s in the 1995 – 2005 period. Keywords: